Resiliensi Pada Janda Cerai Mati - Citra Ayu Kumala Sari; Imasria Wahyuliarmy (Universitas Darul Ulum, 2021)
The purpose of this study is to identify the relationship between social support and resiliency among widows.The The hypothesis proposed in this study is that there is an association between social support and resilience among widows. The subjects in this study were 40 widows whose husbands had died. The sampling technique used in this research was purposive random sampling. The independent variable in this study is social support (X), while the dependent variable is resilience (Y). Hypothesis testing using Rho Spearman Pearson Correlation. Based on the results of hypothesis testing rho = 0.709 with p = 0.000 (p < 0.01), there is a positive and very significant relationship between social support and resilience in divorced widows. The higher the social support, the higher the resilience, vise versa. Keywords: Social Support, Resilience